2018
DOI: 10.1080/17453674.2018.1525195
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint sagittal plane movement in cerebral palsy: a comparative study of 2-dimensional markerless video and 3-dimensional gait analysis

Abstract: Background and purpose — Gait analysis is indicated in children with cerebral palsy (CP) to identify and quantify gait deviations. One particularly difficult-to-treat deviation, crouch gait, can progress in adolescence and ultimately limit the ability to ambulate. An objective quantitative assessment is essential to early identify progressive gait impairments in children with CP. 3-dimensional gait analysis (3D GA) is considered the gold standard, although it is expensive, seldom available, and unnecessarily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Although video motion analysis is routinely performed by prosthetists and orthotists mainly using visual observation [ 51 ], recent literature reported encouraging results of a few applications of video-based 2D gait analysis in children with cerebral palsy [ 52 ] and Parkinson Disease’s adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although video motion analysis is routinely performed by prosthetists and orthotists mainly using visual observation [ 51 ], recent literature reported encouraging results of a few applications of video-based 2D gait analysis in children with cerebral palsy [ 52 ] and Parkinson Disease’s adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both control groups with ligamentous laxity and flat foot were small and should be increased in order to better distinguish the role that these orthopaedic features may play in the gait of FXS children. Furthermore, the gait analysis was performed out of a formal gait laboratory without the aid of a stereophotogrammetric system; by considering the impact of video based motion analysis on the precision of kinematic data, we only included the sagittal plane kinematics, which was found to be consistent with the gait profile generated by the stereophotogrammetric system [ 34 , 52 ]. Finally, in terms of muscle activity, our data displayed a large variability in terms of envelope peak, and this finds agreement with Granata et al [ 58 ], who reported large variability in terms of both envelope and on-off timing of muscle recruitment in children.…”
Section: Discussionmentioning
confidence: 99%
“…Depth cameras, such as the Microsoft Azure Kinect, record standard video and additionally also record the distance between each pixel and the camera (depth). While depth cameras are relatively cheap and accessible, research has demonstrated large differences compared to marker-based methods ( Dolatabadi, Taati & Mihailidis, 2016 ; Mentiplay et al, 2015 ; Natarajan et al, 2017 ; Otte et al, 2016 ; Pantzar-Castilla et al, 2018 ; Rodrigues et al, 2019 ; Tanaka et al, 2018 ). Additionally, depth cameras have limitations on capture rate, capture volume and data collection may require controlled lighting conditions ( Clark et al, 2019 ; Sarbolandi, Lefloch & Kolb, 2015 ).…”
Section: Markerless Motion Capturementioning
confidence: 99%
“…While some markerless systems may be approaching the accuracy of marker-based methods, some applications may not need highly accurate data and instead, numerous trials ( e.g. , numerous walking strides) could be averaged to obtain reliable average results ( Pantzar-Castilla et al, 2018 ). Unfortunately, this approach may be unable to detect small changes over time and it is not always possible to collect many trials in a clinical, rehabilitation or sport setting.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Clinically, three-dimensional gait analysis is considered the gold standard to quantify lower limb movements and its reliability was excellent. 27 By capturing motion data for each joint during walking and calculating parameters such as walking cycle, speed, stride length, step length and foot deviation angle, it is possible to examine the muscle, joint function and coordination related to walking. 28 A walking cycle consists of two parts: the stance phase and the swing phase, where the stance phase accounts for approximately 60% of the cycle, and the swing phase accounts for approximately 40%.…”
Section: Discussionmentioning
confidence: 99%